Javanese People's Acceptance of Arabic Calligraphy as Home Decoration - et al., Retno Purnama Irawati (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The interweaving of Arabic calligraphy letters is a combination of artistic art. Arabic calligraphy is giving rise to aspects of visual beauty that can be enjoyed and created a sense of joy. It can encourage people to get closer to Allah, love for goodness, nobility, and so on. Arabic calligraphy is infused into the hearts of those who see, by the meaning of the text. Apart from being a form of reception for one of the verses in the Koran, namely in the verse al-Kursī, calligraphy has developed in various forms and includes various functions and fields that are indirectly connected with the text of the Quran. Starting from the context of the Koran alone, and the spiritual substance of the Koran that continues to live in all aspects of traditional Islamic calligraphy. Calligraphy is also the choice of Muslims in Central Java to decorate the walls of their homes. The choice of calligraphy to decorate the walls of the house is based on various reasons, ranging from aesthetic, religious, to magical reasons. This research was conducted to conduct a more in-depth analysis of the Central Javanese people's reception of Arabic calligraphy as a home decoration and to analyze the reasons for choosing Arabic calligraphy as a home wall decoration for the Muslim community of Central Java. This research is qualitative research with a phenomenological research design. The data collection technique is done using documentation techniques, interviews, and distributing questionnaires. The questionnaire was created using a combination open and closed question model for all groups of respondents. Data analysis in this study used statistical calculations on respondents' answers to the questionnaire, which were analyzed qualitatively. The research subjects were the Muslim community in Central Java, totaling 164 adults. When viewed from the gender of the respondents, 91 people (or 55% of respondents) were male, and 73 people (or 45% of respondents) were female. Calligraphy is a medium for conveying religious messages through language. The language chosen is a significant or straightforward language that is easy to understand or understand in sentences. The writing style displays beautiful shapes so that the type of style that is elastic or flexible and easy to create is chosen to make a beautiful impression, namely the tsutust and naskhiy types. The artistic expression that most strongly displays the substance of calligraphy is the traditional expression that has been chosen as an artistic expression. Figural and expressionist forms of expression were chosen because of their role in providing new nuances of free calligraphic expression